Variation in the lobar pattern of the right and left lungs: A case report - Esomonu, Ugochukwu Godfrey (Australasian Medical Journal, 2013)
The right lung has three lobes and two fissures while the left lung has two lobes and one fissure. During a routine dissection we observed a variant complete fissure and three incomplete fissures in the right lung while the left lung presented with a variant transverse fissure separating the superior lingual and anterior bronchopulmonary segments. In the right lung, the incomplete fissures lie between the apical and posterior bronchopulmonary segments; medial and lateral bronchopulmonary segments; apical and basal bronchopulmonary segments. The complete variant fissure separates the medial basal bronchopulmonary segment from the remaining basal segments. Such variant fissures and lobes are clinically important in cases of lobotomy.